The Relict Vegetation of Sheo Bari, Sohan Valley in the Hoshiarpur Siwaliks - Puri, G. S. (Indian Forester, 1957)
The relict vegetation of Sheo Bari was studied in the Sohan Valley in the Hoshiarpur Siwaliks. The average annual rainfall is 57.17" and the soil in the valley is a recent alluvium. While the vegetation in the valley is scrubby, consisting of early riverain species like Acacia catechu, Dalbergia sissoo the vegetation at Sheo Bari is mesophytic, having Putranjiva, Albi ia lebbek, Litsea chinensis, etc., in upper canopy and Strobilanthes and Ferns in the ground flora. The course of succession in the Sohan Valley has been indicated and it has been suggested that the mesophytic vegetation could exist in a stable equilibrium in the valley, provided the adverse human interference is excluded. The protection of forests may aim at getting a mesophytic vegetation.